Optimizing Art and Design Education Through Mobile Apps Development - Abednego, Victor Adiluhung; Kusumawati, Yudhistya Ayu; Christyanti, Michelle Gita (Jurnal Bahasa Rupa, 2024)
The rapid growth of the Visual Communication Design sector in the digital era highlights the increasing demand for skilled graphic designers across various industries. As creative professionals, graphic designers are tasked with conveying messages through visual means, balancing aesthetics, functionality, and technical expertise. However, many designers face challenges in producing high-quality work due to limited practical and theoretical knowledge. This research proposes the development of "Dr. Visual," a mobile e-learning app designed to enhance the design skills of both aspiring and young designers. By utilizing the design thinking process, the app aims to provide users with deeper insights into design theory and practice. Employing a Quantitative Descriptive method, the study analyzes user interest in the app, emphasizing its potential to support designers in creating superior artwork. The findings suggest that "Dr. Visual" could serve as a valuable resource, offering a platform for graphic designers to enhance their skills and produce higher-quality designs.